ASEAN DALAM MENYELESAIKAN KRISIS YANG TERJADI DI MYANMAR - Hartana; Kadek Dhyan Wahyuni (Universitas Pendidikan Ganesha, 2021)
Myanmar's Rohingya are a Muslim minority in one of the regions of Myanmar called Rakhine. In this case, Myanmar does not recognize the citizenship of the Rohingya ethnic group. They are one of Myanmar's 135 ethnic groups without official documentation and therefore have no citizenship. Other ethnic groups and governments in Rakhine State have used large-scale violence against them, and Rohingyas have also been forcibly taken to refugee camps or exiled to neighboring countries. The United Nations Refugee Agency As of 2012, more than 168,000 Rohingya had fled Myanmar, with hundreds of thousands more fleeing across the border into Bangladesh since violence resurfaced in August 2017 in connection with the issue under investigation. I'm assuming. right. Indeed, ASEAN's 2007 Declaration on the Protection and Promotion of Migrant Worker Rights focused only on migrant workers and not on refugees. The Rohingya's plight was exacerbated by the response of several Southeast Asian countries in 2015 when they turned back boats carrying thousands of desperate Rohingya. International pressure and media scrutiny over their refusal to help the people on the boat eventually led to Indonesia and Malaysia temporarily allowing the people to land. This has also led to several crackdowns on traffickers involved in transporting Rohingya.